Diferentes fontes de dsRNA para a ativação do mecanismo de RNA de interferência: proteção do camarão Litopenaeus vannamei contra o vírus da mionecrose infecciosa - Nogueira, Luiz Fagner Ferreira (2022)
Aquaculture has been growing dramatically in recent years because of the increase in world demand for proteins of aquatic origin. However, the presence of diseases in cultivated organisms has generated strong drops in production. Recently, the cultivation of marine shrimp Litopenaeus vannamei in Brazil, especially in the northeast region, has been suffering from outbreaks of viral diseases. The infectious myonecrosis virus (IMNV) is endemic to this region and can promote from loss of zootechnical performance to mortality in nurseries around 70%. As an alternative to combat this disease, the RNA interference mechanism, which is activated in the presence of species-specific double-stranded RNA (dsRNA) molecules, has been shown to be an alternative in the treatment of viral diseases in shrimp. However, the production and delivery of these molecules by more viable methods for cultivation need further investigation. The objective of this work is to evaluate the protection of different models of dsRNA expression in vivo against the infectious myonecrosis virus through experimental challenges. In the first chapter, dsRNA-VP28ORF1a molecules were produced by a commercial kit and by the Escherichia coli HT115 strain for therapy via injection and feed of L. vannamei shrimp infected with IMNV. The molecules produced by E. coli and by the commercial kit were not effective in silencing the virus. In chapter two, the protection of dsRNA-VP28ORF1a via Bacillus subtilis strain JJBs3 injected into L. vannamei shrimp challenged with IMNV was evaluated based on viral load, histopathological and gene expression analysis linked to the RNAi mechanism. There was no protection in the groups that received the dsRNAs via injection, but the group that received the virus-related molecules 10 days showed a slower mortality pattern. it was observed that there was modulation of the genes that received these molecules. In chapter three, the protection of the B. subtilis JJBs3 strain expressing dsRNA-VP28ORF1a incorporated into the feed of L. vannamei shrimp experimentally challenged with IMNV was evaluated. The effectiveness of dsRNA molecules was verified by viral load, histopathological and gene expression analysis linked to the RNAi mechanism. The group that received the JJBs3 strain expressing dsRNA-VP28ORF1a had a 49% survival over 17 days of infection and a similar mean viral load (approximately 3.5x10³ viral copies/μg RNA) as the group that did not receive the virus, while the group that received the JJBs6 strain expressing dsRNA unrelated to the virus had 100% mortality in the same period and a higher viral load (1.32x107 viral copies/μg RNA) compared to the JJBs3 group. The results presented in this thesis indicate that the genetically edited B. subtilis strain to produce specific dsRNA can be applied as a potential biological model to combat the infectious myonecrosis virus in farmed shrimp.